The Theme of Lithuanian Independence in the Letters of Halina Didžiulytė-Mošinskienė to the Writers of Anykščiai - Berezauskienė, Audronė (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; summary in English] This article deals with the analysis of the correspondence between Lithuanian culture and society figure, educator and writer Halina Didžiulytė-Mošinskienė (1911–2004) and the writers, journalists and local lore historians Milda Telksnytė-Račkaitienė and Vygandas Račkaitis. The main source of the study is H. Didžiulytė Mošinskienė’s letters written to the Anykščiai writers, which are preserved in the Department of Regional Documents and Local Lore History of the Anykščiai Regional Liudvika and Stanislovas Didžiuliai Public Library. The article studies the activity of Halina Didžiulytė-Mošinskienė and presents the period of Independent Lithuania (1918–1940) reflected in the publications and books of Lithuanian immigrants. Halina Mošinskienė’s letters not only showed some facts of her personal life but also revealed the distinctiveness of her expression. The epistle discourse was helpful in forming her portrait. The letter study has revealed the patriotism of a well-educated person and her efforts in preserving the ties with Lithuania and the native tongue through books and publications. While living abroad, she devoted the energy of her mind and spirit to Lithuania. She contributed significantly to the preservation of Lithuanian language and culture. Besides providing informational, documental and historical value, Halina Mošinskienė’s letters were the connection with those who lived in Lithuania. The letters were a source of hope and strength for the people living far from their homeland. At the same time, these letters had documentary importance for those who stayed in Lithuania.